Review of Macronychiinae (Diptera, Sarcophagidae) of the World - Verves, Yu.G.; Khrokalo, L.A. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2006)
The faunistic and ecological data on 19 species of Macronychia based on 269 specimens and literature are given. Macronychia dolini Verves et Khrokalo, sp. n., M. substriginervis Verves et Khrokalo, sp. n., M. richterae Verves et Khrokalo, sp. n. and M. xuei Verves et Khrokalo, sp. n. are described. The monotypic subgenus Thomaspapeia Verves et Khrokalo, subgen. n. is established for Macronychia malayana Kurahashi et Pape. The original key to all species is provided.